Now and then - Parker, Robert B., 1932-2010 (No exit press, 2008)
Spenser knows something's amiss the moment Dennis Doherty walks into his office. The guy's aggressive yet wary, in the way men frightened for their marriages always are. So when Doherty asks Spenser to investigate his wife Jordan's abnormal behavior, Spenser agrees. A job's a job, after all.Not surprisingly, Spenser catches Jordan with another man, tells Dennis what he's found out, and considers the case closed. But a couple of days later, all hell breaks loose, and three people are dead.